68Ga‐PSMA‐PET/CT staging prior to definitive radiation treatment for prostate cancer. Issue 4 (16th April 2018) - Hruby, George; Eade, Thomas; Emmett, Louise; Ho, Bao; Hsiao, Ed; Schembri, Geoff; Guo, Linxin; Kwong, Carolyn; Hunter, Julia; Byrne, Keelan; Kneebone, Andrew
Abstract: Aim: To explore the utility of prostate specific membrane antigen (PSMA)‐positron emission tomography (PET)/computed tomography (CT) in addition to conventional imaging prior to definitive external beam radiation treatment (EBRT) for prostate cancer. Methods: All men undergoing PSMA‐PET/CT prior to definitive EBRT for intermediate and high‐risk prostate cancer were included in our ethics approved prospective database. For each patient, clinical and pathological results, in addition to scan results including site of PSMA positive disease and number of lesions, were recorded. Results of conventional imaging (bone scan, CT and multiparametric magnetic resonance imaging [MRI]) were reviewed and included. Results: One hundred nine men underwent staging PSMA‐PET/CT between May 2015 and June 2017; all patients had national comprehensive cancer network (NCCN) intermediate or high‐risk prostate cancer and 87% had Gleason score (GS) 4 + 3 or higher. There was positive uptake corresponding to the primary in 108, equivocal in one. All patients with image detected nodal or bony lesions had GS 4 + 3 or more disease. Compared to conventional imaging with bone scan, CT and multiparametric MRI, PSMA‐PET/CT upstaged an additional 7 patients (6.4%) from M0 to M1, 16 from N0M0 to N1M0 (14.7%) and downstaged 3 (2.8%) from M1 to M0 disease. Conclusion: PSMA‐PET/CT identified the primary in 99% of patients, and altered staging in 21% of men with intermediate or high‐risk prostate cancer referred for definitive EBRT compared to CT, bone scan and multiparametric MRI. Following this audit, we recommend the routine use of PSMA‐PET/CT prior to EBRT in this patient group.